Measuring the technological backwardness of middle- and low-income countries: The employment quality gap and its relationship with the per capita income gap - José Luís Oreiro; Stefan Wilson D'Amato; Luciano D'Agostini; Paulo Gala (PSL Quarterly Review, 2022)
The aim of the present article is to further develop the line of research initiated by Oreiro et al. (2019) by expanding the database used to calculate the EQI and the EQG, but also to control the effects of variables other than the EQG, such as the amount of capital per worker, over the PCIG and to assess the impact of the determinants of the EQG, considering both price and non-price factors. Following Tregenna and Andreoni (2020), the EQI will be redefined as the ratio between the share of the workforce in the sectors of high technological intensity with respect to the share of the workforce in the sectors of medium and low technological intensity. The EQG will then be used as an independent variable to explain the behavior of the PCIG of a sample of 47 developing countries in Latin America, the Caribbean, the Middle East, Africa, and Asia from 2001 to 2014.
Keywords: C51; E24; O11; 330; Structural change; economic development; employment quality gap